Prova e Ragione. Struttura e demarcazione dell’epistemologia della VI Ricerca logica attraverso alcuni casi di studio - Masi, Felice (Bollettino Filosofico, 2018)
Can we say that the epistemology of the first phenomenology is a form of verificationism and that the VI Logical Investigation has introduced perception in the “space of reasons”? Can we share what Husserl wrote on the VI Logical Investigation, that is, that it constituted a first step towards a phenomenological theory of reason? These two questions are mirror-like, even though he first one concerns the demarcation of phenomenology with respect to the tradition of classical empiricism and the second with respect to later developments of Husserlian thought, i. e. phenomenological philosophy or transcendental phenomenology. After a first part dedicated to some operational definitions, the essay deals with six study-cases, on the basis of which the conclusion is that the VI Logical Investigation achieves an intersection between theory of provability and reflexive empiricism.